DIGITAL LITERACY, CONTENT CREATOR: ASSISTANCE OF CREATIVE INDUSTRY PLAYERS THROUGH DIGITAL LITERACY FOR PAINTERS IN KAMPUNG LUKIS JELEKONG - Yulia Segarwati; Almadina Rakhmaniar; Novie Sucitrawati Firman; Rahmat Ramdhan (Pasundan International of Community Services Journal (PICS-J), 2022)
Kampung Giri Harja or known as Jelekong village is an art and painting village located in Jelekong Village, Bale Endah District, Bandung Regency. This village was founded by Asep Sunandar Sunarya. Previously, Jelekong Village could be said to be an unknown village, but when Abah Asep Sunandar lived in this village, everything changed. Jelekong village changed its name to Giri Harja Endah Village, then it was known as an art village located in southern Bandung. Because the village of Giri Harja Endah is known as the village of art and painting, many of people are engaged in the arts, especially in the field of wayang golek and in the field of painting. Many residents of Giri Harja Endah are puppeteers and painters and on every street in the village Giri Harja Endah many shops selling paintings and puppets. The problems that have been identified are discussed together by the PKM team (community activity program). In order to be able to provide the best solution, the problem is how the current content creators become qualified so they can help in improving digital media literacy. In this PKM activity, the team will carry out activities based on several methods. The expected output target in this activity is to attract digital media literacy with quality creative content. The approach method used to overcome the problems faced by partners is through socialization, training or counseling and consultation activities. Then an active participatory approach was also carried out between the proposer team and partners on an ongoing basis and played an active role in providing assistance and guidance in the creation of digital creative content.